Oncolytic adenoviruses in bladder and kidney cancers: emerging strategies and next frontiers - Yao, Jia; Shayakhmetov, Dmitry M. (Frontiers in Microbiology, 2025)
Engineering oncolytic adenoviruses (OAds) to treat renal and bladder cancers has advanced rapidly. Leveraging insights into adenovirus biology, the molecular pathology of cancer, and recent progress in tumor immunology, multiple strategies have been developed to enhance the antitumor specificity and overall efficacy of OAds as anticancer therapeutics. Combination with other cancer treatment modalities has shown synergistic effects, further augmenting their therapeutic potential. In this review, we discuss the most recent advances in oncolytic adenovirus designs that tailor this vector platform for the treatment of renal and bladder cancers. We further summarize findings from preclinical animal studies demonstrating tumor suppression by OAds, as well as results from clinical trials evaluating their safety and efficacy in cancer patients. Collectively, the accumulated data highlights the significant potential of engineered oncolytic adenoviruses as a novel therapeutic modality for cancer patients that have limited treatment options.